Effects of omega‐3 fatty acids on cerebral white matter hyperintensities and medial temporal lobe atrophy in older non‐demented adults: A 3‐year randomized‐controlled phase 2 trial: Prevention (nonpharmacological) / Nutrition. (7th December 2020) - Bowman, Gene L; Silbert, Lisa C; Dodge, Hiroko H; Hagen, Kirsten; David, Jason C; Murchison, Charles F; Lahna, David; Kaye, Jeffrey; Quinn, Joseph F; Shinto, Lynne
Abstract: Background: The n‐3 PUFA may modulate risk for age‐related cognitive impairment through vascular mechanisms. MRI derived cerebral white matter hyperintensities (WMH) presumptively reflect small vessel disease and their accumulation increases risk for age‐related cognitive decline and dementia. Blood n‐3 PUFA are consistently associated with reduced WMH and stroke. The primary aim here was to evaluate n‐3 PUFA supplementation on WMH accumulation over 3 years in an older population with evidence of WMH and absence of n‐3 PUFA supplementation. Methods: The study was a double‐blind, placebo‐controlled trial, with participants randomized to a daily dose of fish oil (1650 mg combined eicosapentaenoic acid‐EPA and docosahexaenoic acid‐DHA) or placebo oil (soybean) for a 3‐year intervention. Main inclusion criteria were: non‐demented (MMSE > 24), age > 74 years, WMH volume > 5.0 cc, and plasma n‐3 PUFA (EPA+DHA) < 110 umol/L (or < 5.5 percent of total fatty acids). The primary endpoint was 3‐year change in total WMH volume. Secondary endpoints include changes in regional brain volumes and white matter integrity. Exploratory endpoints include measures of cerebral blood flow, domain‐specific and global cognitive measures with subgroup analyses by APOE4 genotype. A linear mixed‐effects model was used to assess the outcomes. Results: 102 subjects were enrolled (mean age 81±4.4, MMSE 27.8±1.7; 60% female, 27.5% APOE4 positive) and a total of 78 participants completed the trial. Supplementation had no beneficial effect on rate of WMH progression, which increased by a mean of 1.07 cc per year in the n‐3 PUFA group vs 1.12 cc per year in the placebo group (p = 0.30 for time*trial arm interaction). Three‐year changes in executive cognitive function z‐scores were not different between treatment groups (p = 0.24). No differences in adverse events between groups were observed . Conclusion: N‐3 PUFA compared with placebo, failed to slow 3‐year WMH accumulation and executive function decline in older non‐demented adults presenting with evidence of WMH. N‐3 PUFA at the 1.65‐gram dose appears safe in older adults over 3‐years. Additional MRI and cognitive outcomes with detailed safety profiles are planned for presentation.